2011
DOI: 10.1124/dmd.110.035865
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Inhibitory Effects ofN-Butylpyridinium Chloride and Structurally Related Ionic Liquids on Organic Cation Transporters 1/2 and Human Toxic Extrusion Transporters 1/2-K In Vitro and In Vivo

Abstract: ABSTRACT:Ionic liquids (ILs) are a class of salts that are expected to be used as a new source of solvents and for many other applications. Our previous studies revealed that selected ILs, structurally related organic cations, are eliminated exclusively in urine as the parent compound, partially mediated by renal transporters. This study investigated the inhibitory effects of N-butylpyridinium chloride (NBuPy-Cl) and structurally related ILs on organic cation transporters (OCTs) and multidrug and toxic extrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…NBuPy can block both the OCT2-mediated entry of metformin into RPT cells and the MATE1-mediated exit of metformin from these cells (rat kidney expresses MATE1 but not MATE2-K; (Ohta et al, 2006;Klaassen and Aleksunes, 2010)), but the observation that the NBuPy-induced reduction in plasma clearance of metformin was accompanied by an increase in metformin content (3.7-fold) (Cheng et al, 2011) in renal tissue suggests that NBuPy exerted its principal inhibitory effect on the MATE1-mediated exit step. It should be noted that the doses of NBuPy required to inhibit metformin clearance were quite high and most likely resulted in blood levels that would not be achieved in humans exposed orally or dermally to environmental or occupational levels of NBuPy-Cl or other ILs (Cheng et al, 2011). Nevertheless, the results presented here indicate that ILs are potentially capable of interfering with MATE-mediated OC transport and, consequently, of influencing the distribution and pharmacokinetics of cationic compounds that rely on renal (or hepatic) secretory pathways.…”
Section: Mate1mentioning
confidence: 89%
See 3 more Smart Citations
“…NBuPy can block both the OCT2-mediated entry of metformin into RPT cells and the MATE1-mediated exit of metformin from these cells (rat kidney expresses MATE1 but not MATE2-K; (Ohta et al, 2006;Klaassen and Aleksunes, 2010)), but the observation that the NBuPy-induced reduction in plasma clearance of metformin was accompanied by an increase in metformin content (3.7-fold) (Cheng et al, 2011) in renal tissue suggests that NBuPy exerted its principal inhibitory effect on the MATE1-mediated exit step. It should be noted that the doses of NBuPy required to inhibit metformin clearance were quite high and most likely resulted in blood levels that would not be achieved in humans exposed orally or dermally to environmental or occupational levels of NBuPy-Cl or other ILs (Cheng et al, 2011). Nevertheless, the results presented here indicate that ILs are potentially capable of interfering with MATE-mediated OC transport and, consequently, of influencing the distribution and pharmacokinetics of cationic compounds that rely on renal (or hepatic) secretory pathways.…”
Section: Mate1mentioning
confidence: 89%
“…Previous studies showed that the three aforementioned model ILs are, in fact, actively secreted in urine of both mice and rats Knudsen et al, 2009), and they both inhibit and serve as substrate for the human and rat orthologs of OCT2 (Cheng et al, , 2011Knudsen et al, 2009). Although it might reasonably be inferred that secreted ILs are substrates for MATE transporters, the nature of the interaction of ILs with the MATEs has not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular accumulation of compound (at each concentration tested) in the parental (control) HEK Flp-In cells was subtracted from uptake into the cells expressing the individual transporters; this was done to account for potential endogenous transport activity in the control cells. Kinetic parameters, K m (Michaelis constant) and J max (maximal rate of transport), were determined as described previously (Cheng et al, 2011).…”
Section: Cloning Of Transportersmentioning
confidence: 99%